Literasi Lingkungan Hidup dalam Ayat-ayat al-Qur’an - Rafli Rahman; Widya Ningsih; Aldilal; Akbar; Aminudin (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to examine environmental literacy in the verses of the Qur'an and what efforts must then be made to detect these verses. This research uses library research method. The primary sources in writing this article include references that discuss implicitly or explicitly about environmental literacy in the verses of the Qur'an. The obtained references are then edited, coded, reduced, verified and analyzed, to be further studied further in order to find the right understanding related to environmental literacy. The results of this research and discussion show that in the Qur'an there is a command from Allah that commands humans to maintain and pay attention to the environment which is currently a discussion of the crisis in the contemporary era. This study concludes that there are many verses of the Qur'an that discuss the environment which later becomes a proof for mankind and especially for Muslims to always protect the environment in order to create a love relationship with the universe.